Promoting Organizational Learning in Healthcare through Simulation: A Study in Serendipity (Journal of Organizational Psychology, 2017)
In a case study of a simulation-based medical education program, we serendipitously discovered organizational learning as it emerged among expected patterns of individual learning. During simulation debriefings, radiologists-in-training (“residents”) spontaneously engaged in organizational learning processes. They identified routines that hindered patient care for uncommon, but potentially fatal contrast media reactions. We provide exemplars illustrating how residents identified system-related patient safety threats. Residents learned directly from simulation, recollected clinical encounters, and constructed hypothetical histories (imagining what could have happened in their hospitals). We discuss implications for organizational learning from hypothetical histories and future research promoting organizational learning in healthcare through simulation.
Keywords: Organizational Psychology; Healthcare; Medical Education